The collaborative mode by PmSVPs and PmDAMs reveals neofunctionalization in the switch of the flower bud development and dormancy for Prunus mume - Zhao, Kai; Zhou, Yuzhen; Zheng, Yan; Zheng, Rui-yue; Hu, Meijuan; Tong, Yan; Luo, Xianmei; Zhang, Yangting; Shen, Ming-li (Frontiers in Plant Science, 2022)
Prunus mume (Rosaceae, Prunoideae) serves as an excellent ornamental woody plant with a large temperature-range cultivation scope, its flower buds require certain low temperature to achieve flowering circulation. Thus, it is important delving the processes of flower bud differentiation, dormancy, which affected its continuous flowering. These processes are generally considered as the regulation by MADS-box homologs, SHORT VEGETATIVE PHASE (SVP) and DORMANCY- ASSOCIATED MADS-BOX (DAM). However, precise model is needed on their interdependence and specific function when acting as a complex in flower development of P. mume. Therefore, this study highlighted integral roles of PmDAMs and PmSVPs in flower organ development and dormancy cycle. Segregation of PmDAMs and PmSVPs in a different cluster suggested distinct functions and neofunctionalization. The expression pattern and yeast two-hybrid assays jointly revealed that eight genes involved in the floral organ development stages, PmDAM1 and PmDAM5 specifically related to prolificated flowers formation. PmSVP1- 2 mingled in the protein complex in bud dormancy stages with PmDAMs. Finally, we proposed hypothesis that PmSVP1 and PmSVP2 could combine with PmDAM1 to have effect on flower organogenesis and interact with PmDAM5 and PmDAM6 to regulate flower bud dormancy. These findings could help expand the current molecular mechanism based on MADS-box genes during flower bud development and dormancy.